Preserved effector functions of human ORAI1- and STIM1-deficient neutrophils - Elling, Roland; Keller, Baerbel; Weidinger, Carl; Häffner, Monika; Deshmukh, Sachin D.; Zee, Isabelle; Speckmann, Carsten; Ehl, Stephan; Schwarz, Klaus; Feske, Stefan; Henneke, Philipp (Journal of allergy and clinical immunology, 2016)
[...]we compared expression levels of ORAI and STIM homologues between PMNs, B lymphocytes, and T lymphocytes by using publicly available RNA sequencing data from healthy subjects.7 ORAI1 and STIM1 were similarly expressed in PMNs and lymphocytes. [...]mRNA levels of the different ORAI and STIM homologues are comparable across leukocyte subsets (see Fig E1 in this article's Online Repository at www.jacionline.org). [...]FcÎ³RIII (CD16) cross-linking also induced Ca2+ influx in ORAI1 p.R91W PMN that was only moderately reduced compared with that in control PMNs (see Fig E4 in this article's Online Repository at www.jacionline.org). Because cytosolic Ca2+ concentrations are considered essential for antibacterial PMN functions, we examined whether ORAI1 deficiency impaired the PMN response to various microbial and nonmicrobial ligands.